Penetapan Wali Hakim Sebagai Pengganti Wali Adlal Yang Tidak Menyetujui Pernikahan Anaknya - Elang Darmawan; Ahmad Baihaki; Otih Handayani (KRTHA BHAYANGKARA, 2021)
Humans are gifted by God Almighty to be able to reproduce and continue their offspring. The marriage order in Indonesia is regulated in the rules of marriage law. including Law no. 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). In the KHI it is stated that the guardian of marriage in marriage is a pillar that must be fulfilled for the prospective bride who acts to marry her. Problems occur when lineage guardians are reluctant to marry off their children due to parental considerations regarding the seeds, bebet and the weight of the prospective son-in-law. This study aims to examine the application of positive legal rules or norms which are then linked to the discussion that is the subject of discussion. Normative juridical law research is carried out by examining formal legal rules such as laws, regulations and literature containing theoretical concepts. The results of the study describe that the determination of the guardian of the judge as a substitute for the guardian of Adlal can be done by using the correct marriage mechanism, the marriage cannot be prevented or canceled because the bride and groom have met the requirements of marriage and there is no marriage ban